2014
DOI: 10.1088/1367-2630/16/3/033015
|View full text |Cite
|
Sign up to set email alerts
|

Experimental evidence of super-resolution better thanλ/105 with positive refraction

Abstract: Super-resolution (SR) systems surpassing the Abbe diffraction limit have been theoretically and experimentally demonstrated using a number of different approaches and technologies: using materials with a negative refractive index, utilizing optical super-oscillation, using a resonant metalens, etc. However, recently it has been proved theoretically that in the Maxwell fish-eye lens (MFE), a device made of positive refractive index materials, the same phenomenon takes place. Moreover, using a simpler device equ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
23
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 18 publications
(47 reference statements)
0
23
0
Order By: Relevance
“…Much of the controversy has centred on the role of detection in perfect imaging-the perfect transfer of the electromagnetic field from object to image is only possible if the image is detected. Another important point was noticed in a computer simulation [18] and a subsequent experiment [19] by Miñano et al: at specific resonance frequencies of the instrument a point detector is sensitive to displacements of a point source with an accuracy that is significantly better than the diffraction limit. No physical explanation for this feature has been found yet.…”
mentioning
confidence: 99%
“…Much of the controversy has centred on the role of detection in perfect imaging-the perfect transfer of the electromagnetic field from object to image is only possible if the image is detected. Another important point was noticed in a computer simulation [18] and a subsequent experiment [19] by Miñano et al: at specific resonance frequencies of the instrument a point detector is sensitive to displacements of a point source with an accuracy that is significantly better than the diffraction limit. No physical explanation for this feature has been found yet.…”
mentioning
confidence: 99%
“…We should also note that the 'super-resolution' found in SGW is at near field in their simulation [22,23] and experiment [24] (i.e., the closest distance between the source and the physical waveguiding structure is less than the wavelength). In near-field, a super-resolution can be easily achieved by some microscope technologies (e.g., using a grating in the near field to make the conversion between the evanescent and propagating waves in a structured illumination microscopy [27], and nearfield scanning optical microscope [28]).…”
Section: About the 'Super-resolution' In A Spherical Geodesic Waveguidementioning
confidence: 93%
“…Later Miñano's group also claimed that λ/500 and λ/3000 super-resolution can be achieved in the SGW for only some discrete frequencies by numerical simulations [22,23]. In 2014, they claimed their experiment of the SGW could achieve a λ/105 resolution for a set of specific frequencies and loads [24]. Actually the 'super-resolution' found by Miñano in an SGW is essentially different from the perfect image in an MFEL/MFEM claimed by Leonhardt due to the following reasons:…”
Section: About the 'Super-resolution' In A Spherical Geodesic Waveguidementioning
confidence: 99%
See 1 more Smart Citation
“…This drawback, known as the "Abbé limit, has long been the foremost barrier to high-resolution imaging, until the early 2000s when Pendry [1] showed that an optical lens with a negative index can restore the evanescent waves issued from the source allowing then for the subdiffraction imaging and for a resolution better than half the wavelength at the focus. From then on, several devices based on this principle, including superlensing photonic crystals [2], optical superlenses [3], hyperlenses [4,5], metalenses [6][7][8][9], and Maxwell fish eyes [10,11], have been proposed. These artificial devices either restore the evanescent waves [1][2][3], or convert them to propagative waves owing to a subwavelength grating inserted in between the object and the objective of a regular optical microscope [4][5][6].…”
mentioning
confidence: 99%